Intralesional corticosteroid injections for the treatment of oral lichen planus: A systematic review - Aliyah Alsubhi; Noura Salem; Maryam Mohab; Bashaer Alghamdi; Nouf Alghamdi; Raniya A Alasiri; Rajwa A Sindi; Raneem A Almastadi; Noor M Alfayez; Mawaddah Alsulaimani; Weaam Alsheikh; Sana Alhamed; et al. (Wolters Kluwer Medknow Publications, 2020)
Background: Oral lichen planus is a chronic, immune-mediated disease that can impact the oral cavity significantly. Treatment options include topical and systemic corticosteroid therapy based on the disease severity. Intra-lesional corticosteroid injections (ILCI) have been incorporated in clinical practice as an effective modality to deliver treatment locally to expedite the healing process while limiting systemic toxicity. Purpose: The objective of this systematic review was to evaluate the role of ILCI in treating OLP. Methods: A systematic review of the literature was conducted in the PubMed and Web of Science databases following PRISMA protocol and up to September 2019. All English-language literature on ILCI for OLP was included. Relevant articles were systematically reviewed using multiple levels of elimination by title, abstract, and full text. Data from the included studies were extracted and analyzed. A total of six studies met the inclusion criteria. Results: Triamcinolone acetonide intra-lesional injection demonstrated efficacy and rapid healing of OLP lesions in three studies. Minor adverse events of secondary oral candidiasis and cushingoid features were reported. Conclusion: ILCI may be considered as an effective treatment option for OLP lesions with minimal side effects and risk of disease relapse.